Sosialisasi penerapan cooperative learning tipe Team Games Tournament (TGT) pada SMK Negeri Kota Makassar - Djen Djalal (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The objectives that can be achieved from thisprogram are: to socialize the implementation of theCooperative Learning model of the Team Game Tournament(TGT) type at SMK Negeri 3 Makassar. The problem faced bypartners is that the teacher still uses the direct learning modelwhere the teacher is actively involved in carrying out thecontents of the lesson to students. By doing this, it can limitthe creativity space of students to construct their ideas. Themethod used in this activity is lecture, question and answer andfield practice carried out for a week. This program is veryuseful for the physical education teachers and students at SMKNegeri 3 Makassar in increasing their knowledge and understandingof the Cooperative Learning model of the TeamGame Tournament (TGT) type. Moreover, they can apply theTGT type to the physical education subject in their school. Theresults of the implementation of this program show that theinterest of physical education teachers at SMK Negeri 3Makassar in participating in the socialization of the applicationof Cooperative Learning model in the Team GameTournament (TGT) type was very high. For the students, theapplication of this model will improve their motivation in thelearning process. Thus, it can improve student learningoutcomes.